The Influence of Cash Turnover and Inventory Turnover on Profitability with Liquidity as an Intervening Variable (An Empirical Study on Companies in the Clothing and Luxury Goods Subsector Listed on the Indonesia Stock Exchange from 2021 to 2023) - Nur Puspita, Lovia; Tiswiyanti, Wiwik; Hernando, Riski (Faculty of Economics and Business Universitas Jambi, 2025)
This research aims to determine the effect of cash turnover and inventory turnover on profitability with liquidity as an intervening variable. The independent variables used in this study are cash turnover and inventory turnover. While the dependent variables in the study are profitability and liquidity as intervening variables. This type of research is quantitative research. The population in this study were companies in the clothing and luxury goods sub-sector listed on the Indonesia Stock Exchange for the period 2021-2023. The sample in this study was taken using the purposive sampling method with a sample size of 19 companies. Data analysis in this study is multiple linear regression analysis with the help of the IBM SPSS version 26 program. The data in this study are secondary data obtained from the official website of the Indonesia Stock Exchange. The results of this study indicate that cash turnover has an effect and inventory turnover does not affect liquidity. Cash turnover and inventory turnover have no effect but liquidity affects profitability. Hypothesis testing using the Sobel test shows that liquidity is able to indirectly mediate the relationship between cash turnover and profitability, but has not been able to mediate the relationship between inventory turnover and profitability.